Regeneration and histological study of somatic embryogenesis of sugarcane (Saccharum officinarum L.) cultivar PS 864 - Fitri Damayanti; Suharsono Suharsono; Aris Tjahjoleksono; Ika Mariska (The East Java Biological Society, 2018)
The process affecting somatic embryo formation in sugarcane is very specific for each genotype, so the determination of the best somatic embryo regeneration medium in sugarcane clones is necessary. The objective of this study was to determine the concentration of Benzine Amino Purine (BAP) and Kinetin for somatic embryo maturation and to observe the maturation stage for somatic embryo of sugarcane cultivar PS 864. Maturation of the nodular callus was conducted by addition of Kinetin (0, 1, 3, and 5 mg/L) and BAP (0 and 5 mg/L) in solid and liquid medium. The medium was optimized using glutamine. The medium for somatic embryo germination used full and half strength Murashige and Skoog medium (MS) supplemented with 20 g/L sucrose and amino acid or growth regulator (BAP and NAA). Nodular callus well grew in solid medium, whereas callus become browning and not existence of somatic embryo maturation in liquid medium. The highest number of globular embryos (38 embryos) was produced from MS medium supplemented with 1 or 3 mg/L Kinetin combined with 5 mg/L BAP. The highest number of scutellum (21 embryos) and coleoptile (19 embryos) resulted from 3 mg/L Kinetin. The MS medium with full strength was added with 100 mg/L glutamine that was the best germination medium. This medium resulted the highest percentage of somatic embryo (73.29%) forming bipolar structure, and the largest number of leaves (4.58). Histological analysis showed that somatic embryos of sugarcane emerged from many cells through the budding process and also initiated from one cell.